1967
DOI: 10.1126/science.155.3770.1640
|View full text |Cite
|
Sign up to set email alerts
|

Late Pleistocene History of Coniferous Woodland in the Mohave Desert

Abstract: Seventeen ancient wood-rat middens, ranging in radiocarbon age from 7400 to 19,500 years and to older than 40,000 years, have been uncovered in the northeastern, north-central, southeastern, and southwestern sectors of the Mohave Desert. Excellent preservation of macroscopic plant materials (including stems, buds, leaves, fruits, and seeds) enables identification of many plant species growing within the limited foraging range of the sedentary wood rat. An approximately synchronous zonal differentiation of vege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
0

Year Published

1975
1975
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(101 citation statements)
references
References 18 publications
5
96
0
Order By: Relevance
“…The influence of P l e i s t o c e n e climatic fluctuations on the expansions and c o n t r a c t i o n s of species ranges is well documented. These effects have been amplified r e c e n t l y by the w o r k on rat middens and p a l y n o l o g y in the s o u t h w e s t e r n United States (King, 1973; M e h r i n g e r et al 1970; Van D e v e n d e r & King, 1971;Wells, 1965Wells, , 1966Wells, , 1970Wells & Berger, 1967;Wright, 1970;Whitehead, 1972). The floristic a f f i n i t i e s b e t w e e n the Edwards p l a t e a u of central Texas and the Sierra Madre of Nuevo Leon and C o a h u i l a has existed since the Tertiary (Axelrod, 1958).…”
Section: Discussion the P A T T E R N Of P O P U L A T I O Nmentioning
confidence: 95%
“…The influence of P l e i s t o c e n e climatic fluctuations on the expansions and c o n t r a c t i o n s of species ranges is well documented. These effects have been amplified r e c e n t l y by the w o r k on rat middens and p a l y n o l o g y in the s o u t h w e s t e r n United States (King, 1973; M e h r i n g e r et al 1970; Van D e v e n d e r & King, 1971;Wells, 1965Wells, , 1966Wells, , 1970Wells & Berger, 1967;Wright, 1970;Whitehead, 1972). The floristic a f f i n i t i e s b e t w e e n the Edwards p l a t e a u of central Texas and the Sierra Madre of Nuevo Leon and C o a h u i l a has existed since the Tertiary (Axelrod, 1958).…”
Section: Discussion the P A T T E R N Of P O P U L A T I O Nmentioning
confidence: 95%
“…At such a time, sclerophyllous vegetation must have shifted northward, into the present Namib and a good part of the western Karoo, where some relict patches exist today, as well. Such a shift parallels that of the pinyon pine-juniper woodland down into the present deserts of western North America during the last glacial (Wells 1966, Wells & Berger 1967. Inasmuch as there probably were four shifts of this order during the past 2.7 m.y., adaptation to the present desert environment need not be attributed to great antiquity.…”
Section: Subtropic Woodland-scrubmentioning
confidence: 86%
“…This suggests that as recently as the last pluvial period, the Cape flora may have been far more widespread (Levys 1938), a relation paralleled by the nature of the plants recovered from late Pleistocene wood rat middens of the Mohave Desert and border areas (e.g. Wells & Berger 1967). Levyns (1964) suggested that the youthfulness of the flora in its present mediterranean-climate environment is implied also by the growth rhythms of some of the taxa.…”
Section: Cape Vegetationmentioning
confidence: 94%
“…The flora of the pinyon-juniper woodland is relatively rich in shrubs , cacti, and perennial herbs; annuals are, as in the more mesic white fir-juniper - Figs Gilia, Mentzelia, Nemophila, Phacelia, Thysanocarpus, and Vulpia. Further information on the pinyon-juniper woodlands of the eastern Mojave Desert and their more important components can be obtained from Bradley and Deacon (1967), Castagnoli, de Nevers, and Stone (1981), Hart, Stein, and Warrick (1979), Lanner (1974), Mooney (1973), Prigge (1975), Reveal (1944), Roof (1978), Thome (1976Thome ( , 1979, Trombulak and Cody (1980), Twisselmann (1967) , Vasek (1966) , Vasek and Thome (1977) , Wells and Berger (1967);and West, Rea, and Tausch (1975).…”
Section: Pinyon-juniper Woodlandmentioning
confidence: 99%